2019
DOI: 10.1108/lht-01-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

Information visualization skills for academic librarians

Abstract: Purpose The purpose of this paper is to investigate how scholars in the digital humanities employ information visualization techniques in their research, and how academic librarians should prepare themselves to support this emerging trend. Design/methodology/approach This study adopts a content analysis methodology, which further draws techniques from data mining, natural language processing and information visualization to analyze three peer-reviewed journals published within the last five years and ten onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Examples include collecting library data from multiple data sources to data analytics platforms for visualization and further analysis (Harisanty et al. , 2022; Chen, 2019), and transferring invoice data from library management systems to the universities' finance office for payment processing (Chiu, 2013; Lee et al. , 2006).…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include collecting library data from multiple data sources to data analytics platforms for visualization and further analysis (Harisanty et al. , 2022; Chen, 2019), and transferring invoice data from library management systems to the universities' finance office for payment processing (Chiu, 2013; Lee et al. , 2006).…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
“…(2) Data collection, conversion, and importsuch as collecting data held in other systems, converting them to certain formats, data cleansing, joining and merging data, and importing them to other systems. Examples include collecting library data from multiple data sources to data analytics platforms for visualization and further analysis (Harisanty et al, 2022;Chen, 2019), and transferring invoice data from library management systems to the universities' finance office for payment processing (Chiu, 2013;Lee et al, 2006).…”
Section: Library Applicationsmentioning
confidence: 99%
“…There has been a lot of research on information visualization in the DH and library education, but there has not been much discussion of how these two fields overlap. Particularly, less is known about the implementation of library training in support of DH research (Chen, 2019). LISTA DLP 39,3 claimed that the "digital humanities" term first was used in the LIS literature in the year 1998 issue of Information Technology and Libraries in a two-page report on The National Initiative for a Networked Cultural Heritage (Zhang et al, 2015).…”
Section: Digital Humanities In the Librarymentioning
confidence: 99%
“…It indicated that the coated fabric and aramid fabric had good water repellency. The reason for the water repellency of coated fabric was that the ordered molecular orientation of methyl groups with low surface tension of the silicone resin in the coating solution (Chen et al, 2009).…”
Section: Water Repellent Performancementioning
confidence: 99%